PRR34-AS1 promotes mitochondrial division and glycolytic reprogramming in hepatocellular carcinoma cells through upregulation of MIEF2 - Yang Xuejing; Feng Huijing; Kim Jonghwa; Ti Gang; Wang Lin; Wang Kun; Song Dong (Acta Biochimica et Biophysica Sinica)
LncRNA PRR34-AS1 overexpression promotes the proliferation and invasion of hepatocellular carcinoma (HCC) cells, but whether it affects HCC energy metabolism remains unclear. Mitochondrial division and glycolytic reprogramming play important roles in tumor development. In this study, the differential expression of PRR34-AS1 is explored via TCGA analysis, and higher levels of PRR34-AS1 are detected in patients with liver cancer than in healthy individuals. A series of experiments, such as CCK-8, PCR, and immunofluorescence staining, reveal that the proliferation, invasion, glycolysis, and mitochondrial division of PRR34-AS1-overexpressing hepatoma cells are significantly promoted. TCGA analysis and immunohistochemistry reveal high expression of the mitochondrial dynamin MIEF2 in liver cancer tissues. Dual-luciferase reporter assays confirm that miR-498 targets and binds to mitochondrial elongation factor 2 (MIEF2). In addition, we show that PRR34-AS1 can sponge miR-498. Therefore, we further investigate the effects of the lncRNA PRR34-AS1/miR-498/MIEF2 axis on the growth, glucose metabolism, and mitochondrial division in hepatocellular carcinoma cells. A series of experiments are performed on hepatocellular carcinoma cells after different treatments. The results show that the proliferative activity, invasive ability, and glycolytic level of hepatocellular carcinoma cells are decreased in HCC cells with low PRR34-AS1 expression, and the miR-498 expression level is increased in these cells. Inhibition of miR-498 or overexpression of MIEF2 restored the proliferative activity, invasive ability, glycolysis, and mitochondrial division in hepatocellular carcinoma cells. Thus, PRR34-AS1 regulates MIEF2 by sponging miR-498, thereby promoting mitochondrial division, mediating glycolytic reprogramming and ultimately driving the growth and invasion of HCC cells. Furthermore, in vivo mouse experiments yield results similar to those of the in vitro experiments, verifying the above results.